PROCESSOS INFLAMATÓRIOS DO COLO E DA VAGINA: "UMA REVISÃO" - Maud Filho, Francisco; Carneiro, Márcia Mendonça; Molinari, Marcelo Braga; Molinari, Eduardo Braga; Molinari, Rogério Braga (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento